Factors Affecting Early Marriage among Female Adolescents: A Path Analysis Evidence from Blora, Central Java - Wella Anggraini; Pawito Pawito; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2019)
Background: Early marriage is a phenomenon which has been a controversy to this day. The prevalence of early marriage in Indonesia has decreased, namely in 2013 by 24% and decreased by 1% in 2015. The purpose of this study was to analyze the factors that influence early marriage in Blora, Central Java, using a path analysis model.Subject and Method: This was a cross sectional study conducted in Blora, Central Java, from September to October 2019. A sample of 200 married women within 5 years was selected by random sampling. The dependent variable was early marriage. The independent variables were parental income, peer support, society culture, parental support, daughter's status, attitude, subjective norms, perceived control of behavior (PBC), and intention. The data were collected by questionnaire analyzed by path analysis run on Stata 13.Results: The likelihood of early marriage in adolescents increased with strong intention (b= 2.06; 95% CI= 3.00 to 1.13; p <0.001) and low family income (<Rp. 1,650,000) (b= 1.83; CI 95% = 2.68 to 0.98; p<0.001). The likelihood of early marriage was decreased with weak status of girls in families (b= -1.71; 95% CI= -2.61 to -0.80; p<0.001) and strong peer support to not do early marriage (b= -2.08; 95% CI= -2.98 to -1.19; p<0.001). Early marriage was indirectly affected by attitude through society culture, intention through family support, intention through attitude, intention through perceived behavioral control, and family support through subjective norm.Conclusions: The likelihood of early marriage in adolescents increases with strong intention and low family income. The likelihood of early marriage is decreased by weak status of girls in families and strong peer support to not do early marriage. Early marriage is indirectly affected by society culture, family support, attitude, PBC, and subjective norm.Keywords: early marriage, adolescentsCorrespondence: Wella Anggraini. Masters Program of Public Health Science, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: wellaanggraini89@gmail.com. Mobile: 081215216795Journal of Health Promotion and Behavior (2019), 4(4): 287-297https://doi.org/10.26911/thejhpb.2019.04.04.05